ПРИНЦИПИ ПОБУДОВИ ІНВАРІАНТНИХ ПІДСИЛЮВАЛЬНО- ПЕРЕТВОРЮВАЛЬНИХ СИСТЕМ З ПРОГНОЗУВАННЯМ ДЛЯ АПАРАТНИХ ЗАСОБІВ АВТОНОМНИХ ОБ'ЄКТІВ - Самков, О.В.; Смирнов, В.С.; Штіфзон, О.Й.; Любицький, С.В.; Лізанець, В.В. (Інститут електродинаміки Національної академії наук України, 2017)
The construction principles of structure-invariant amplification and conversion systems (ACS) on the basis of pulse-code modulation (PCM) are considered. The advantages of an adaptive delta modulation (DM) usage in a digital signal processing are presented and an operation of a functional circuit of the adaptive DM-encoder is considered. The operation of extrapolator analyzer unit is described. A two-channel structural organization of a power path of the conversion system is proposed to eliminate signal distortions due to instantaneous zero level of the input voltage when using a single-phase AC voltage supply. Referenses 9, figures 10.